Social organization and homicide rates in Chicago neighborhoods: the role of structural stability and change. Issue 4 (7th August 2020) - Becker, Jacob H.
ABSTRACT: A life-course perspective on neighborhood effects suggests that levels of and changes in neighborhood structural conditions may impact neighborhood social organization, collective efficacy, and reciprocated exchange, with implications for changes in homicide rates. Results indicate changes in neighborhood disadvantage – though not in immigrant concentration or residential stability – disrupt both reciprocated exchange and collective efficacy. However, neither mechanism appears to mediate the change-homicide relationship, nor do the two mediators significantly interact in their association with homicide rates. Findings suggest both contemporary and historical neighborhood disadvantage is significantly related to homicide rates, supporting a dynamic view of the links between conditions, social mediators, and homicide.